Upaya Penanggulangan Tindak Pidana Pencabulan Terhadap Anak di Kota Padang - Rahmat Fauzi (Fakultas Hukum, Universitas Warmadewa, 2020)
Crimes against children are rampant in the Padang City. Based on data obtained from the Padang City Police in 2014 there were 2 cases, in 2015 there were 5 cases, in 2016 there were 6 cases and in 2017 there were 7 cases, evidently molestation on children increased. The increasing number of criminal acts of sexual abuse that occur require serious handling in tackling and providing legal protection. The purpose of this study was to find out efforts to tackle the crime of sexual abuse of children in the city of Padang. The research approach used is a sociological juridical approach, namely the presentation and study of the relationship of legal aspects with non-legal aspects in the operation of law in reality. The results showed that the efforts to tackle the crime of sexual abuse of children in the city of Padang in the form of pre-emptive, preventive and repressive measures.